Socialization of Dangerous Goods to High School Students - Ahmad Soimun; Anggun Prima Gilang Rupaka; Tertib Sinuligga; Putu Ayu Govika Krisna Dewi; Anisa Mahadita Candra Rahayu (Politeknik Trasportasi darat Bali, 2022)
In this current era, Community Service (PKM) is a very useful thing to improve people's quality of life, heavy traffic on the road creates a lot of risk of accidents, especially high school students who still need a lot of understanding about road safety including knowing everything. symbolic of roads and regulations on highways, one of which needs to be known is the cargo of dangerous goods that require special handling, all goods and types of goods and their conditions endanger the safety and health of the public, through several lecturers and cadets involved, Land Transportation Polytechnic Bali carries out community service activities to SMA 1 Baturiti Tabanan Regency by referring to the information on Dangerous Goods in increasing students' knowledge about the cargo of dangerous goods. With this PkM socialization, the expected goal is to increase students' awareness of safety in their environment and to know the transportation of dangerous goods and to know the function and purpose of the Placard display in the vicinity, because if they do not know the dangers of dangerous goods, they will pose a threat to the safety of students. This activity is carried out using the mediation method with counseling which aims to increase understanding and awareness about the cargo of Dangerous Goods.